[Kertas kerja] Bengkel introduction to Corrosion, Radiography and Analytical Techniques for Preservation of National Heritage di MINT Bangi, 8-12 Disember 2003 - Bengkel introduction to Corrosion, Radiography and Analytical Techniques for Preservation of National Heritage (2003: Bangi); Institut Penyelidikan Teknologi Nuklear Malaysia; Malaysia. Jabatan Muzium dan Antikuiti (Kuala Lumpur : Jabatan Muzium dan Antikuiti, 2003)
Mengandungi kertas kerja yang dibentangkan dalam Bengkel'Introduction to Corrosion, Radiography and Analytical Techniques for Preservation of National Heritage' yang di adakan di MINT, Bangi
Copy available in DVD format
VHS Format
Keywords: Historic preservation -- Malaysia; Antiquities -- Collection and preservation; Cultural property -- Protection